Recommended physical activity and all cause and cause specific mortality in US adults: prospective cohort study - Zhao, Min (BMJ, 2020)
OBJECTIVE: To determine the association between recommended physical activity according to the 2018 physical activity guidelines for Americans and all cause and cause specific mortality using a nationally representative sample of US adults. DESIGN: Population based cohort study. SETTING: National Health Interview Survey (1997-2014) with linkage to the National Death Index records to 31 December 2015. PARTICIPANTS: 479 856 adults aged 18 years or older. EXPOSURES: Participant self-reports of the amount of leisure time spent in aerobic physical activity and muscle strengthening activity each week were combined and categorised into four groups: insufficient activity, aerobic activity only, muscle strengthening only, and both aerobic and muscle strengthening activities according to the physical activity guidelines. MAIN OUTCOME MEASURES: All cause mortality and cause specific mortality (cardiovascular disease, cancer, chronic lower respiratory tract diseases, accidents and injuries, Alzheimer’s disease, diabetes mellitus, influenza and pneumonia, and nephritis, nephrotic syndrome, or nephrosis) obtained from the National Death Index records. RESULTS: During a median follow-up of 8.75 years, 59 819 adults died from all causes, 13 509 from cardiovascular disease, 14 375 from cancer, 3188 from chronic lower respiratory tract diseases, 2477 from accidents and injuries, 1470 from Alzheimer’s disease, 1803 from diabetes mellitus, 1135 from influenza and pneumonia, and 1129 from nephritis, nephrotic syndrome, or nephrosis. Compared with those who did not meet the physical activity guidelines (n=268 193), those who engaged in recommended muscle strengthening activity (n=21 428; hazard ratio 0.89, 95% confidence interval 0.85 to 0.94) or aerobic activity (n=113 851; 0.71, 0.69 to 0.72) were found to be at reduced risk of all cause mortality; and even larger survival benefits were found in those engaged in both activities (n=76 384; 0.60, 0.57 to 0.62). In addition, similar patterns were reported for cause specific mortality from cardiovascular disease, cancer, and chronic lower respiratory tract diseases. CONCLUSIONS: Adults who engage in leisure time aerobic and muscle strengthening activities at levels recommended by the 2018 physical activity guidelines for Americans show greatly reduced risk of all cause and cause specific mortality. These data suggest that the physical activity levels recommended in the guidelines are associated with important survival benefits.